Epinephrine May Contribute to the Persistence of Traumatic Memories in a Post-traumatic Stress Disorder Animal Model - Martinho, Raquel; Oliveira, Ana; Correia, Gabriela; Marques, Márcia; Seixas, Rafaela; Serrão, Paula; Moreira-Rodrigues, Mónica (Frontiers in Molecular Neuroscience, 2020)
The importance of catecholamines in post-traumatic stress disorder (PTSD) still needs to be explored. We aimed to evaluate epinephrine’s (EPI) causal role and molecular mechanism for the persistence of PTSD traumatic memories. Wild-type (WT) and EPI-deficient mice (phenylethanolamine-N-methyltransferase-knockout mice, Pnmt-KO) were induced with PTSD and behavioral tests were performed. Some Pnmt-KO mice were administered with EPI or vehicle. Catecholamines were quantified by HPLC-ED. Nr4a1, Nr4a2, and Nr4a3 mRNA expression were evaluated by real-time PCR in hippocampus samples. It was observed an increase in EPI and freezing behavior, and a decrease in open arm entries in the elevated plus-maze test and time spent in the light in the light–dark test in WT mice in the PTSD-induction group compared to control. After induction of PTSD, Pnmt-KO mice showed a decrease in freezing, as well as an increase in open arm entries and transitions between compartments compared to WT. After PTSD induction, Pnmt-KO mice administered with EPI showed an increase in freezing compared with the vehicle. On day 0 of PTSD induction, it was observed an increase in mRNA expression of Nr4a2 and Nr4a3 genes in the hippocampus of WT mice compared to control, contrary to Pnmt-KO mice. In conclusion, our data suggest that EPI may be involved in the persistence of traumatic memories in PTSD, possibly through enhancement of the expression of Nr4a2 and Nr4a3 genes in the hippocampus. Peripheral administration of EPI restored contextual traumatic memories in Pnmt-KO mice, which suggests a causal role for EPI. The persistence of contextual traumatic memories may contribute to anxiety-like behavior and resistance of traumatic memory extinction in this PTSD mice model.